Development of Elementary School Social Sciences Textbooks Based on Partner Collaboration to Improve PGSD Students' 21st Century Skills - Slamet Widodo; Adhy Putri Rilianti (Jurnal Pena Karakter : Jurnal Pendidikan Anak dan Karakter, 2025)
The elementary social studies course at PGSD STKIP Al Hikmah Surabaya uses a textbook containing concepts and theories written by the lecturer. Textbook does not contain material that can facilitate students to practice in the school so that students' 21st century skills are weak. Based on the results of measuring students' 21st century skills consisting of aspects of communication, collaboration, critical thinking and problem solving, creativity and innovation, 75% of students have not yet completed it, while the remaining 25% have completed it. To solve this problem, a solution is needed in the form of developing elementary school social studies textbooks based on partner collaboration to improve students' 21st century skills. The aim of this research is to produce a collaboration-based elementary social studies textbook to improve the 21st century skills of PGSD students that is valid, reliable, and practical. In this research, the Research and Development (RnD) method was used involving 30 PGSD students at STKIP Al Hikmah as research subjects. The data collection methods used consisted of interviews, questionnaires, observation and expert review. The 4D Model used in this RnD research consists of four stages, namely define, design, develop, and disseminate. This research produces an elementary school social studies textbook that is valid, reliable and practical. These results are shown from expert assessments, readability tests, and trials that obtained high scores.